Percutaneous access to coronary arteries in patients after transcatheter aortic valve implantation procedures – is it a real problem? - Chodór, Piotr; Wilczek, Krzysztof; Przybylski, Roman; Nożyński, Jerzy; Włoch, Łukasz; Kalarus, Zbigniew (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2019)
Transcatheter aortic valve implantation (TAVI) is still developing and changing our approach to treating patients with severe symptomatic aortic stenosis. Aortic stenosis frequently coexists with coronary artery disease. Both diseases have similar risk factors for their development and one should expect a future progression of coronary artery disease. The current guidelines have expanded TAVI indications to include intermediate-risk patients, and perhaps they will be expanded to include low-risk patients in the future. Survival after TAVI in younger patients will depend on the durability of the aortic valves and methods of coronary artery disease treatment. This paper presents some aspects of performing coronary angiography and percutaneous coronary intervention in patients who had TAVI performed using the two most popular aortic valves – balloon expandable aortic valves (Edward Sapien/Edward Sapien XT/Sapien 3) and self-expandable aortic valves (CoreValve/Evolut R) – on the basis of several examples. This paper also focuses on technical aspects associated with a proper implantation of aortic valves to ensure easy access to coronary arteries, as well as on possible problems when the implantation is not optimal. We discuss interactions between the structure of the aortic valve stent, catheters, commissures of new aortic valves, and coronary ostia.